(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The discussion on the ambit of right to the truth in International Law has deepened in contemporary times. The aspect of right to the truth is of paramount importance in terms of International human rights and International criminal justice. It is evident that human suffering in the shape of atrocities like war, genocide, and other conflicts against humanity are real and happening. These circumstances implicate immense psychological and emotional distress on the victim. It is here that the need to know the truth arises, so that the victim gets an opportunity to come across reality. It also helps in divulging the truth and it facilitates the judicial process in the end and helps to achieve the transitional justice that is vouched. There are several vital forums namely international human right courts, truth commissions, and international criminal courts that are in existence for the protection of rights to life and prohibition of torture against victim in furtherance of transnational justice. Moreover, it is evident that right to the truth in general parlance arises in situations wherein a particular state fails to deal with atrocities using their own civil and criminal procedures. It is here that the matter attracts concerns and invokes jurisdiction of international entities. Through this research manuscript, an attempt is made to understand and analyse the role of aspect of right to the truth in the development of victim jurisprudence. Another aspect of the manuscript contributes, suggests, and hits the core of the international debate on the right of a victim to the truth. Ultimately, it attempts to ring the bell at the right time and is an appropriate read for the enthusiasts of International Criminal law and those who have zeal to acknowledge the realities of a victim.